PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING DI SENGKALING KULINER â€œSEKULâ€ MALANG - Amrullah, Wahyu (Manajemen Bisnis, 2017)
The research is to analyze experiential marketing consisting of sense, feel, think, act, and relate, customer satisfaction, customer loyalty and to analyze impact of experiential marketing on customer loyalty through customer satisfaction as an intervening variable at Sengkaling Kuliner ?SeKul? Malang. Use data from quetionnaires of the sample 100 respondents with purposive sampling technic. This research is descriptive quantitative study with survey method. Test instrument used include the validity and reliability test. Analysis data method used is a range of scale, path analysis, and hypothesis testing. The result of the calculation of experiential marketing consisting of sense, feel, think, act, and relate scale range is gene1rally categorized as good. Customer satisfaction and customer loyalty based on the result of the calculation of the scale range is generally categorized as high. These result indicate that the effect of indirectly greater than the direct effect of this proves that customer satisfaction to intercede or mediate the effect of experiential marketing to customer loyalty. This indicates that the experiential marketing significant effect on the customer loyalty through customer satisfaction.